2005
DOI: 10.1177/106480460501300303
|View full text |Cite
|
Sign up to set email alerts
|

Naive Realism: Misplaced Faith in Realistic Displays

Abstract: A theory of why users and display designers prefer highly realistic, supposedly intuitive displays despite their poor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 31 publications
8
131
0
1
Order By: Relevance
“…Thus our results are consistent with the somewhat counterintuitive theoretical claim (Betrancourt, 2005;Krygier et al, 1997) that limited interactivity may sometimes be more effective than full interactivity. This point is reminiscent of research by Smallman and St. John (2005) regarding misplaced faith in 3D displays in which they show that performance with 2D displays is superior for many tasks.…”
Section: Discussionmentioning
confidence: 89%
“…Thus our results are consistent with the somewhat counterintuitive theoretical claim (Betrancourt, 2005;Krygier et al, 1997) that limited interactivity may sometimes be more effective than full interactivity. This point is reminiscent of research by Smallman and St. John (2005) regarding misplaced faith in 3D displays in which they show that performance with 2D displays is superior for many tasks.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, readers may judge their comprehension on the basis of belief about multimedia presentations. Previous studies have suggested that people believe that realistic images improve their performance on tasks such as detecting changes (e.g., Levin, Momen, Drivdahl, & Simons, 2000;Smallman & St. John, 2005). If so, the format in which neuroscientific information is presented may affect not only the credibility of neuroscientific information, but also metacomprehension judgment, because brain images are realistic.…”
mentioning
confidence: 99%
“…One disadvantage with photorealistic representations is that they provide the users with too much information that obscures the main message. Furthermore, there are results from the field of psychology stating that users have a too strong belief in highly realistic displays [32]. This belief might result in users putting a higher trust in photorealistic representations.…”
Section: Visual Rule Checkingmentioning
confidence: 99%